Groundwater well fields in ice-margin valley aquifers - is it easy to protect them, or not? An overview of hydrogeological and legal aspects of determining wellhead protection zones - Matusiak, Magdalena; Górski, Józef; Dragon, Krzysztof; Kruć-Fijałkowska, Roksana (Geologos, 2024)
This paper discusses principles for delineating wellhead protection zones (WHPZ) of groundwater well fields in ice-margin valleys. A distinctive feature of such well fields is that, apart from the often geogenically contaminated water of ice-margin valleys, they are largely supplied with high-quality water from intertill aquifers of neighbouring uplands. However, much of this inflow can be intercepted by wells for agriculture that are increasingly being constructed in the capture zones of existing municipal well fields, thus posing a threat to the quality of water for the public. This problem has been investigated using the example of a municipal well in Wroniawy (Poland) by analysing changes in the recharge components of this well field with a groundwater flow model. The results indicate that the commissioning of agricultural abstractions in the capture zone of this well field reduces inflow from intertill aquifers (8.5 per cent) and precipitation recharge (3.3 per cent), following a change in the extent of the capture zone. The loss of these qualitative recharge components is substituted by an increase in poor-quality water, i.e., surface water (7.3 per cent) and geogenically contaminated water from the ice-margin valley centre (3.8 per cent). Protecting well fields in such locations from adverse water quality changes requires the implementation of quantitative shielding of best-quality water, calling for WHPZ to cover the entire capture zone regardless of water flow timing, which is not provided for in Polish legislation. Costs and constraints of implementing such a WHPZ can be reduced by dividing it into sectors that differ in the scope of limitations, with the only quantitative protection applied to the outermost, medium- and low-vulnerable parts of the capture zone.